Evaluating Patients' and Neonatologists' Satisfaction With the Use of Telemedicine for Neonatology Prenatal Consultations During the COVID-19 Pandemic - Lapadula, Maria C.; Rolfs, Shanna; Szyld, Edgardo G.; Hallford, Gene; Clark, Tracie; McCoy, Mike; McKnight, Stephanie; Makkar, Abhishek (Frontiers in Pediatrics, 2021)
ABSTRACT Background: During the COVID-19 pandemic, telemedicine plays a critical role in providing safe, effective healthcare services, while reinforcing social distancing and optimizing the use of personal protective equipment. In this context, the Oklahoma Children’s Hospital implemented virtual neonatology prenatal visits for pregnant women with a diagnosis of fetal anomalies. While tele-consultations have been broadly used with a high degree of acceptance in rural and remote areas, satisfaction has not been assessed in this particular scenario, where patients and physicians discussing sensitive healthcare information had to rapidly adjust to this new modality. Objectives: To evaluate patients’ and neonatologists’ satisfaction with virtual prenatal consultations in the context of the COVID-19 pandemic and to compare satisfaction levels of patients receiving virtual consultation with those receiving in-person consults. Methods: This cross-sectional study evaluated patients’ and neonatologists’ satisfaction with virtual consultations. Participants included pregnant women with diagnosis of fetal anomalies who received neonatology prenatal consultations at Oklahoma Children’s Hospital, either in-person or through telemedicine, from May to mid-November 2020, and neonatologists providing virtual prenatal consultations in the same period. Virtual visits were delivered via Zoom Pro™. Patients and physicians who agreed to participate rated acceptability completing an anonymous 5-point Likert scale survey. Item frequencies and means for categories of items were computed by group (video-consult patients, in-person patients, physicians) and analyzed, using Welch’s t for unequal sample size. Results: Overall consultation quality was rated good or excellent by 35 (100%) video-consult patients and 12 (100%) in-person patients. Patient group means computed on six 5-point Likert items about patient-physician communication did not differ significantly, video-consult: M=28.71 (2.22); in-person consult: M=28.92 (1.78) (p=0.753263). All eight physicians (100%) agreed or strongly agreed that telemedicine was effective, using a 5-point Likert scale, and their combined consultation quality score computed on 10 survey questions was high: M=46.4 (3.11). Conclusion: Despite patient inexperience with tele-consultations, the quick implementation of telemedicine, and the sensitive reason for the visit, patients and physicians were highly satisfied with virtual visits. Telemedicine is a safe, effective alternative for providing neonatology prenatal consultations for pregnant women with diagnosis of fetal anomalies during the pandemic.